1982
DOI: 10.1007/bf01654701
|View full text |Cite
|
Sign up to set email alerts
|

Nitroprusside‐ and nitroglycerin‐induced hypotension: Effects on hemodynamics and on the microcirculation

Abstract: After a short summary of the effects and metabolism of sodium nitroprusside (SNP) and nitroglycerin (NTG), the influence of induced hypotension on hemodynamics and on the microcirculation is investigated. The continuous registration of the local tissue pO2 in skeletal muscle, myocardium, and liver with the multiwire surface electrode provides the opportunity to recognize immediately a change in the microcirculatory bed. This new method shows in animal experiments that the local oxygen supply during SNP‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Hauss et al (6) found that SNP-induced hypotension (4 pg kg-I min-') in dogs caused a reduced oxygenation in skeletal muscle, which was claimed to be due to a reduced oxygen supply. It was also stated that the changes in skeletal muscle oxygen pressure distribution could be due to a redistribution of blood flow to a higher perfusion in "high flow capillaries".…”
Section: Discussionmentioning
confidence: 99%
“…Hauss et al (6) found that SNP-induced hypotension (4 pg kg-I min-') in dogs caused a reduced oxygenation in skeletal muscle, which was claimed to be due to a reduced oxygen supply. It was also stated that the changes in skeletal muscle oxygen pressure distribution could be due to a redistribution of blood flow to a higher perfusion in "high flow capillaries".…”
Section: Discussionmentioning
confidence: 99%
“…No patient in group E suffered from clinically significant bradycardia <50/min, These findings are comparable with the finding of E Ornstein et al [8] with mean heart rate of 67+ 10 in esmolol group in which they compared isoflurane with esmolol and sodium nitroprusside in patients with Arterio-venous malformations.The mean heart rate in group N as per table no 1 is consistent with the fact that nitroglycerine causes either no change or slight tachycardia during continuous infusion as slight increase in heart rate is reflex phenomenon, baroreceptor response secondary to hypotension produced. [9] The mean arterial pressure MAP preoperatively in group E was 88.48+4.28 whereas in group N it was 87.76+4.62 mmHg which were statistically comparable (p>0.05). At 5 th minute the mean MAP in group E was 69.96+2.24 and in group N was 67.28+1.33 mmHg which was statistically significant, (P<0.05).…”
Section: Haemodynamic Variabilitymentioning
confidence: 74%
“…On the other hand, NTG causes either no change or slight tachycardia which is a reflex phenomenon, produced secondary to hypotension. [5] None of our patients in Group N had reflex tachycardia (HR >120 beats/min). This could be because we maintained the MAP within the desired range by titrating the dose of NTG, thereby not allowing hypotension to occur further and produce reflex tachycardia.…”
Section: Discussionmentioning
confidence: 89%